2014
DOI: 10.1044/2014_ajslp-13-0126
|View full text |Cite
|
Sign up to set email alerts
|

Speech-Language Pathology and Concussion Management in Intercollegiate Athletics: The Miami University Concussion Management Program

Abstract: Successful management of sport-related concussion requires an interdisciplinary team that understands the unique neurobehavioral and neurocognitive symptoms associated with sports concussions. SLPs can play a valuable role on the interdisciplinary team in the prompt and appropriate management of postconcussion symptoms so that athletes can successfully return to their athletic, academic, and social activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Kroshus and Baugh add to this the need for concussion education to be "theory-driven and population appropriate" (p. 187), as well as be developed collaboratively by scholars and students working in a variety of academic disciplines. It seems, then, an interdisciplinary approach (Kroshus & Baugh, 2016;Porter, Constantinidou, & Marron, 2014;Tator, 2012) to concussion education on college campuses that is grounded in a process-focused theoretical framework is most likely to beget the desired behavioral changes (increased concussion reportage). In the current study, a team of interdisciplinary researchers, three with backgrounds in athletic training and sports medicine and two with backgrounds in communication, have come together to evaluate and improve the efficacy of the concussion education program at our home institution.…”
mentioning
confidence: 99%
“…Kroshus and Baugh add to this the need for concussion education to be "theory-driven and population appropriate" (p. 187), as well as be developed collaboratively by scholars and students working in a variety of academic disciplines. It seems, then, an interdisciplinary approach (Kroshus & Baugh, 2016;Porter, Constantinidou, & Marron, 2014;Tator, 2012) to concussion education on college campuses that is grounded in a process-focused theoretical framework is most likely to beget the desired behavioral changes (increased concussion reportage). In the current study, a team of interdisciplinary researchers, three with backgrounds in athletic training and sports medicine and two with backgrounds in communication, have come together to evaluate and improve the efficacy of the concussion education program at our home institution.…”
mentioning
confidence: 99%
“…Chinn and Porter (2013) found that a majority of athletic trainers indicated that they communicated directly with instructors to coordinate academic accommodations for student-athletes. In contrast, Knollman-Porter et al (2014) found that it was the role of concussion clinic speech language pathologists to coordinate and notify professors of accommodations. Since policies related to coordinating concussion management may differ by institution, it may not be clear to students to whom they should report if they sustain a concussion, potentially increasing the likelihood that they do not seek supports.…”
Section: Concussion Managementmentioning
confidence: 98%
“…Expert literature (n = 10) provided symptom-specific accommodations to address individualized student care, [37][38][39][40]46,47,57,62,68 but little empirical work (n = 4) has addressed how accommodations might be tailored to individual student needs. 15,80,82,95 Recent evidence has pointed to the clinical value of identifying phenotypes of concussion, 129 both to determine highest risk for complicated recovery and to specify treatment approaches. 123,[130][131][132] Development of protocols for identifying subtypes, matching accommodations, and monitoring for early referral for rehabilitation in high-risk students would likely be of high value to RTL protocols.…”
Section: Critical Elements Of Return To Learn For Students With Concu...mentioning
confidence: 99%
“…Twenty-two (39.2%) articles investigated athletes or sports-related concussion. 10,73,[79][80][81][82][83][84][85][86][87][88][89][90] Intervention data from 37 studies (66.1%) were observational or survey data. Only 2 studies reported on controlled interventions 63,83 ; both targeted concussion education training programs to schools and change in knowledge and concussion management practices.…”
Section: Experimental Designs and Participantsmentioning
confidence: 99%